ANALYSIS OF FACTORS AFFECTING THE VALUE OF INDONESIAN FISHERIES EXPORT TO FIVE DESTINATION COUNTRIES YEARS 2011 TO 2018 - Pratama, Bagus Narendra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This study aims to determine the effect of real GDP, real exchange rates, export prices, and inflation onÂ the export value of Indonesian fisheries from 2011 to 2018. This study uses panel data with a common effectÂ model estimated by the Stata 14 program. The results show that partially the variables Importers' realÂ GDP, export prices based on FOB, and Indonesian inflation have a significant positive effect on the value of Indonesian fisheries exports to destination countries. Meanwhile, the real exchange rate of Indonesia against the currency of the importer country partially has a significant negative effect on the value of Indonesian fisheries exports to the destination country. Keywords: Indonesian Fisheries Exports, Importers Real GDP, RER, FOB Export Prices, Exporter Inflation.